Sociodemographic Profile of Encephalocele Patients in Department of Surgery, Neurosurgery Division, Dr. Mohammad Hoesin General Hospital From 2015-2019: A Retrospective Study - Maleakhi Hasudungan Sinaga; Agung Muda Patih (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2021)
Background: Encephalocele is a collection of congenital diseases characterized by protrusion of brain tissue with or without protrusion of the meninges through a defect in the skull.1 Incidence of encephalocele is found in 1 in 35.000 live births in North America and Europe. Five Types of encephalocele based on anatomical location have different patterns, where in western countries it is reported that it is more often located in the occipital area, whereas in Southeast Asia the frontoetmoidal type is more frequently reported. geographic.3 On this basis, this study was carried out. Methods: This research is a retrospective study with a descriptive design. Data taken from January 1st, 2015 to December 31st, 2019. Results: There were 27 encephalocele patients with complete medical record data with the most distribution being women, age range 1 month to 1 year, work of self-employed parents, ethnic Sumatran parents, region of occipitocervical lesions, onset of action 1 month to 1 year, and the most complications. is a cele rupture Conclusion: The level of parental awareness and appropriate management of all medical personnel determine the prognosis of encephalocele sufferers.